Identification And Analysis Of Organizational Arrangements For Village Owned Enterprises - Hidayat, Arif; Sugiarto, Laga; Sulistianingsih, Dewi; Adhi, Yuli Prasetyo (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement), 2023)
The purpose of this community service activities is to provide understanding for village apparatus and the community in terms of identifying and analyzing the organizational arrangements of Village-Owned Enterprises. Each village has the authority to create and develop BUMDes. BUMDes is one of the indicators towards a prosperous village. Forming BUMDes is still a separate problem for villages, because it is not easy to set up a BUMDes. Preparations are needed to carry out the establishment of BUMDes. Corporate governance is also important because good governance will create success for the BUMDes themselves. Tanuharjo Village, Alian District, Kebumen Regency took the initiative to create BUMDes with village potentials, namely in agriculture and tourism. The establishment of BUMDes is not an easy thing to do and must be done with administrative completeness.